Pengaruh Ownership Concentration, Board Independence, dan Firm Size terhadap Cost of Equity pada Perusahaan Sub Sektor Pertambangan Batu Bara yang Terdaftar dalam Bursa Efek Indonesia Tahun 2019-2023 - Nadya Natasya Ghaida; Irsan Tricahyadinata (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of ownership concentration, board independence, and firm size on the cost of equity in coal mining sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This research uses a quantitative approach with panel data regression analysis. The population of this study consists of coal mining sub-sector companies listed on the Indonesia Stock Exchange, totaling 25 companies. The sampling technique used purposive sampling based on specific criteria to obtain companies that meet the research requirements during the observation period. The data used are secondary data obtained from company financial statements. The results show that ownership concentration has a negative and significant effect on the cost of equity, board independence has a positive but insignificant effect on the cost of equity, and firm size has a positive and significant effect on the cost of equity. Simultaneously, ownership concentration, board independence, and firm size significantly affect the cost of equity. These findings imply that ownership structure and company size are important factors to be considered by investors and management in determining the company’s cost of equity